2019
DOI: 10.3390/pr7010021
|View full text |Cite
|
Sign up to set email alerts
|

Model for Thin Layer Drying of Lemongrass (Cymbopogon citratus) by Hot Air

Abstract: Lemongrass is a plant that contains aromatic compounds (myrcene and limonene), powerful deodorants, and antimicrobial compounds (citral and geraniol). Identifying a suitable drying model for the material is crucial for establishing an initial step for the development of dried products. Convection drying is a commonly used drying method that could extend the shelf life of the product. In this study, a suitable kinetic model for the drying process was determined by fitting moisture data corresponding to four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 21 publications
(31 reference statements)
7
35
0
Order By: Relevance
“…Drying rate curves became steeper as drying temperature increased. This finding is in agreement with observations of several studies on IR drying [ 21 , 22 , 44 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Drying rate curves became steeper as drying temperature increased. This finding is in agreement with observations of several studies on IR drying [ 21 , 22 , 44 ].…”
Section: Resultssupporting
confidence: 94%
“…Moreover, results showed that higher drying temperature resulted in greater slope and the drying time is reduced by about 250%. The data obtained from many other studies in this field support this result [ 3 , 43 , 44 , 49 , 50 , 51 ]. Drying rate curves became steeper as drying temperature increased.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Lemongrass (Cymbopogon citratus), which belongs to the Cymbopogon family [3], consists of about 55 species and is cultivated mainly in tropical and subtropical countries. Lemongrass is a highly organoleptic spice in culinary applications and a common medicinal herb which is extensively used in folk medicine [4,5]. The lemongrass essential oil accounts for more than 75% of the weight of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…He found the peanut-drying curve equation by the least-squares method. Nguyen et al [13] a suitable kinetic model for the drying process was determined by determining the moisture data corresponding to four different temperature levels (50, 55, 60 and 65 • C). In addition, they estimated the effect of drying temperature on dehumidification rate, effective diffusion coefficient and activation energy using seven different drying models.…”
Section: Introductionmentioning
confidence: 99%